2014
DOI: 10.1016/j.gie.2013.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of incomplete resection and perforation associated with endoscopic submucosal dissection for colorectal tumors

Abstract: Poor endoscopic operability and SM deep invasion were significant independent predictors of incomplete resections. Poor endoscopic operability and severe fibrosis were significant independent predictors of perforation. These features may provide helpful information when planning colorectal ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
151
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 145 publications
(159 citation statements)
references
References 35 publications
(48 reference statements)
5
151
1
2
Order By: Relevance
“…Poor endoscopic operability was also reported to be related with perforation (24). The rate of poor endoscopic operability was reported as 45.3%.…”
Section: Difficult Factors Of Colorectal Esdmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor endoscopic operability was also reported to be related with perforation (24). The rate of poor endoscopic operability was reported as 45.3%.…”
Section: Difficult Factors Of Colorectal Esdmentioning
confidence: 99%
“…Right-sided colon tumors, fibrosis, poor endoscopic operability and deep submucosal invasion are reported to be significantly associated with incomplete en bloc resection (6,24). We previously analyzed difficult factors of colorectal ESD using 405 consecutive colorectal ESD cases performed only by an expert in our institution (25) Table 2).…”
Section: Difficult Factors Of Colorectal Esdmentioning
confidence: 99%
“…Factors such as large tumor size, laterally spreading tumors, tumor location (right-sided colon), submucosal injection without hyaluronic acid, severe fibrosis, and deep-submucosally invasive cancer were associated with a higher rate of perforation in other studies [8,10,20,21] . On the other hand, poor endoscopic operability was also reported to be related with perforation [22] . However, our study showed that difficult manipulation was not related with perforation during ESD.…”
mentioning
confidence: 99%
“…Commonly, endoscopic operability in colorectal ESD is due to many factors such as the operator's skill, breathing movement, heartbeat, and adhesion in the colorectum. Only one study reported detail analysis of poor endoscopic operability [22] . It defined poor endoscopic operability as the paradoxical movement of the endoscope, poor control for adhesion, and lesion movement with each heartbeat or breathing.…”
mentioning
confidence: 99%
See 1 more Smart Citation